Effects of coastal marsh conversion to shrimp aquaculture ponds on sediment nitrogen fixation - Liu, Cheng; Li, Niu; Shao, Xuexin; Gao, Dengzhou; Xia, Jiangbao; Cui, Qian; Zhang, Dongjie (Frontiers in Marine Science, 2022)
As a common reclamation practice in global estuaries and coasts, conversion of natural wetlands to aquaculture ponds for food demand had significant effects on nitrogen (N) cycling processes. However, the response of sedimemt N fixation process on this conversion remains poorly understood. Here, slury incubation experiment combined with 15N isotope tracing method and molecular analysis technique were used to investigate the influences of conversion of natural marshland to shrimp ponds on sediemt N fixation process. The results showed that conversion of natural marshland to shrimp ponds significantly promoted sediment N fixation rate. The increasing of sediment N fixation rate may be mainly attributed to the change of sediment EC, TOC and Fe2+/Fe3+ rather than the change of N fixation gene abundance. In addition, there was no obvious difference in sediment N fixation rate between 5-year-old shrimp ponds and 18-year-old shrimp ponds, which may be ascribed to the increasing inhibiting effect of inorganic N concentration with reclamation time. Overall, our findings highlighted that conversion of natural wetlands to aquaculture ponds can affect the N budgets in estuarine and coastal regions by altering the sediment N fixation process.